Developing Android Educational Games Application for Enhancing Children’s Healthy Food Skill - Kandriasari, A; Riska, N; Yulianti, Y (KnE Social Sciences, 2019)
This study aims to develop Edu game of “Ayo Memasak Bersama” that is feasible and effective to improve procedural cognitive about making a healthy food menu for kindergarten children in group B. The research design used Research and Development (R&D) with Borg & Gal model. Respondents were 20 children. Data collection techniques used include observation, interviews, and questionnaires. The product produced is feasible, the material expert’s feasibility test of 98% with the criteria of ”Fulfilling the feasibility aspect.” The media expert has obtained a feasibility test of 96% with the criteria of ”Fulfilling the feasibility aspect.” Based on the feasibility assessment of operational field trials (final field trials) by students, the results revealed 95% with the criteria of ”Feasible.” By using android Edu game of “Ayo Memasak Bersama,” there is an increase of effectiveness in procedural cognitive early childhood with a value of 88.4% with the criteria of ”high product effectiveness.” Keywords: development, Android educational games, healthy food, increasing knowledge, skills, children aged 5-6 years